The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1097/iae.0000000000001959
|View full text |Cite
|
Sign up to set email alerts
|

Internal Limiting Membrane Peeling in Macular Hole Surgery; Why, When, and How?

Abstract: Internal limiting membrane peeling improves MH closure rates but can have several consequences on retinal structure and function. Adjuvants to aid peeling, instrumentation, technique, and experience may all alter the outcome. Hole size and other variables are important in assessing the requirement for peeling and potentially its extent. A variety of evolving alternatives to conventional peeling may improve outcomes and need further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 115 publications
0
68
0
2
Order By: Relevance
“…[71][72][73] In general, it is thought that large, chronic, and myopic macular holes may benefit from ILM peeling, while small, recent macular holes may not need ILM peeling in all cases. 74 A cost-effectiveness analysis was also performed alongside a RCT and concluded that ILM peeling is a cost-effective treatment for FTMH compared to no-peeling technique over a 6-month period and was based on the higher number of reoperations required in the no-peel arm of the trial. 75 Indocyanine green (ICG), trypan blue (TP), brilliant blue (BB), and other dyes, as well as triamcinolone acetonide (TA), have been reported to optimize visualization of the ILM during surgery.…”
Section: P189mentioning
confidence: 99%
“…[71][72][73] In general, it is thought that large, chronic, and myopic macular holes may benefit from ILM peeling, while small, recent macular holes may not need ILM peeling in all cases. 74 A cost-effectiveness analysis was also performed alongside a RCT and concluded that ILM peeling is a cost-effective treatment for FTMH compared to no-peeling technique over a 6-month period and was based on the higher number of reoperations required in the no-peel arm of the trial. 75 Indocyanine green (ICG), trypan blue (TP), brilliant blue (BB), and other dyes, as well as triamcinolone acetonide (TA), have been reported to optimize visualization of the ILM during surgery.…”
Section: P189mentioning
confidence: 99%
“…VA improvement largely depends on pre-operative VA, MH size, and symptoms duration. [1,16,18] In 2001, the American Academy of Ophthalmology published an ophthalmic technology assessment report investigating and reporting the accumulated knowledge regarding the treatment of MHs. [7] This report was based on a broad literature review that included three multicentered randomized controlled trials (RCTs) comparing surgery versus observation for MHs.…”
Section: Treatment Modalities For Mhs Vitrectomymentioning
confidence: 99%
“…Being a relatively rigid membrane, removal of the ILM aids hole closure by improving retinal compliance. [16] ILM peeling further helps healing by removing vitreous cortex residues which can exert traction after surgery, eliminating the bed for fibrocellular proliferation surrounding the hole, and promoting glial cell proliferation which was found to improve hole contraction [16,18,22]…”
Section: Rationalementioning
confidence: 99%
See 2 more Smart Citations